Differences in Learning Achievement of Sedentary and Non-Sedentary Students in Class X High School Students at Al-Arifin Sampang Islamic Boarding School - Hasanah, Uswatun; Afandi, Afandi (LP2M IAI Al-Khairat Pamekasan, 2023)
Research with a significance level of 5% found that t-count = 0.385 while t-table at a significant level of 5% is 2.000. This can be interpreted that t count < t table. Thus Ha is rejected and Ho is accepted, meaning that there is no difference between the learning achievements of students who live and those who do not live in Al-Arifin Islamic Boarding School. This study uses a quantitative method, a research method based on the philosophy of positivism, used to examine certain populations or samples. Data collection uses research instruments and data analysis is quantitative in nature with the aim of testing the hypotheses that have been set. The results of the study showed that there was no difference in achievement between students who lived and those who did not live at the Al-Arifin Islamic boarding school. There are several factors that affect the level of success of students in learning that affect learning achievement.‎